Rancang Bangun Sistem Monitoring Asap Rokok di Toilet Sekolah Menggunakan Sensor MQ-7 dan Transceiver nRF24L01+ dengan Output Suara Berbasis Modul ISD 1820 - Mahdalena, Feby Husna; Firmawati, Nini; Rasyid, Rahmat (Universitas Islam Negeri Imam Bonjol Padang, 2020)
A cigarette smoke monitoring system in school toilets has been designed using MQ-7 sensor and transceiver nRF24L01+ with ISD 1820 module based sound output. This hardware system consists of two units that is a transmitter and receiver. The transmitter unit consists of a MQ-7 sensor, a transceiver circuit nRF24L01+, Arduino Uno R3. The receiver unit consists of transceiver circuit nRF24L01+, LCD, Arduino Uno R3, ISD 1820 module. The MQ-7 sensor functions to detect carbon monoxide gas in cigarette smoke. MQ-7 sensor characterization obtained transfer function y = 0.0635x + 0.3808 with a regression value of R2 = 0.9808. The error value obtained from the comparison of gas read by the MQ-7 sensor with a biogas analyzer is 5.35%. The transceiver nRF24L01+ test obtained that the maximum distance of data transmission is 502 m without barrier and 68 m with wall barrier. The overall design of the device can function properly, the MQ-7 sensor can detect carbon monoxide gas as far as 110 cm and when the concentration is more than 1 ppm the speaker on the ISD 1820 module will be activated as a warning alarm.